Economics of reinvestment on rubber in the estate sector - Samarappuli I N; Dias D B S B; Wickramaratne C S (Journal of the Rubber Research Institute of Sri Lanka, 1997)
Replanting of rubber is considered as a long term investment. This study investigates the financial viability of reinvestment on rubber with especial reference to estate sector in Sri Lanka. Economic life span of a 33-year period is considered for the discounted cash flow analysis. The sample consisted of 135 rubber fields randomly selected from 15 large estates. The total investment for the first six years of immature period consisted of Rs. 129.500/ha. The cost of mature upkeep rangaed from Rs.18.000 to Rs. 29.000 per hectare per year. The average cost per tree inclusive of both investment and running cost accounted for Rs. 2350 = per life span. The discounted cash flow analysis revealed a NPV of Rs. 65.700 at 15;discount rate. The B/C ratio, Net Benefit-Investment ratio, IRR and Pay Back Period were 1.35, 2.80, 22;and 11 years respectively. Certain parameters were varied through sensitivity analysis to assess the economic viability of reinvestment on rubber under different scenarios.
Keywords: Economics; Replanting; Rubber